Women of Three Nations in Indonesian Resurrection: a Feminist Approach on “Jejak Langkah - Rumah Kaca” - Joko Susilo; Niko Fediyanto; Muhammad Junaedi (Proceedings of The ICECRS, 2017)
"Jejak Langkah - Rumah Kaca" is the final part in the tetralogy of Pulau Buru by Pramoedya Ananta Toer. The story is about the beginning of the nations unity movement in Indonesia. Started with human consciousness of Indonesia about equality of rights, it then build the power to compete, competing with the European community. It was the beginning of the 20th century that was called as the beginning of the rise of the Indonesian. This article discusses about three female characters in the story " Jejak Langkah - Rumah Kaca", namely Ang san Mei, Princes van Kasiruta, and Siti Soendari. They came from three different nations, namely Tionghoa, Ambon and Java. The characters are analyzed using Feminist theory. The result shows the appearance in power of behavior and thinking of the three female characters from different nationalities and religions to arouse nationalism in the society. The character of each different character confuses the Gubermen (Government of the Dutch East Indies).